Strategi Pengembangan Usaha Thrifting menggunakan Bisnis Model Canvas (Studi Kasus pada Usaha Supply Point) - Nova Fairus; Palupi Permata (MAMEN: Jurnal Manajemen, 2025)
This study aims to analyze the business model and development strategy of Supply Point, a micro, small, and medium enterprise (MSME) specializing in restored branded second-hand shoes in Lembang, West Bandung Regency. The research adopts a descriptive qualitative approach using a case study method. Data were collected through interviews, observation, and documentation, and analyzed using the Business Model Canvas (BMC) and SWOT analysis frameworks. The findings reveal that Supply Point excels in product restoration quality and actively engages in digital marketing through platforms such as Instagram and TikTok. However, it faces internal challenges including limited human resources, manual inventory management, and the absence of a physical retail space. The study identifies significant development opportunities in the growing sustainable fashion trend, digital MSME transformation, and collaborations with communities and local influencers. Recommended strategies include product diversification, enhanced customer service, inventory digitalization, and the exploration of new distribution channels such as pop-up stores. By strengthening key elements of the BMC and responding strategically to external factors through SWOT analysis, Supply Point has the potential to thrive as a leading player in the preloved footwear industry that is adaptive, sustainable, and highly competitive.